Influence of genetic variants in the apolipoprotein A5 and C3 gene on lipids, lipoproteins, and its association with coronary artery disease in Indians - Bhanushali, Aparna A. (Springer-Verlag, 2010)
Indians worldwide demonstrate a triad of elevated triglyceride (TG) with high low-density lipoprotein cholesterol and low high-density lipoprotein cholesterol levels. In the present study, we aim to investigate the effect of −1131T > C, −3A > G, c.56 C > G, and c.553 G > T SNPs in the apolipoprotein A5 (APOA5) gene and 1100C > T and 3238C > G in the apolipoprotein C3 (APOC3) on plasma lipid and lipoprotein levels and risk of coronary artery disease (CAD) in Indians. Genotyping and lipid assays were carried out using standard protocols in a study population that included 150 controls and 90 cases with CAD. Significant associations between minor alleles and higher TG levels were seen for −1131T > C (P < 0.001), −3A > G (P < 0.001), c.56C > G (P = 0.026), and c.553G > T (P = 0.003) SNPs in the APOA5 gene and 1100C > T (P = 0.001) and 3238C > G (P = 0.009) in the APOC3 gene. The haplotypes 11211, 22111, 11112, and 22112 were significantly associated with TG levels (P = 0.025, P = 0.017, P = 0.027, and P < 0.001, respectively) and very-low-density lipoprotein cholesterol levels (P = 0.025, P = 0.017, P < 0.001, and P = 0.002) in males. The 22111, 11112, and 22112 were associated with elevated TG (P = 0.030, P = 0.036, and P = 0.024) but not VLDL-C levels in females. No association with other lipid parameters was seen. In the logistic regression model, the rare S2 allele was a significant risk factor (P = 0.030, 95% CI 1.186–31.432) along with smoking (P < 0.0001, 95% CI 2.018–10.397) for CAD. The APOA5 and APOC3 locus is a strong determinant of plasma TG levels in Indians. The APOC3 3238G is a risk factor for CAD and a higher frequency was also seen with type 2 diabetes mellitus.